2014
DOI: 10.2967/jnumed.114.141895
|View full text |Cite
|
Sign up to set email alerts
|

Respective Performance of 18F-FDG PET and Radiolabeled Leukocyte Scintigraphy for the Diagnosis of Prosthetic Valve Endocarditis

Abstract: Echocardiography plays a key role in the diagnosis of infective endocarditis (IE) but can be inconclusive in patients in whom prosthetic valve endocarditis (PVE) is suspected. The incremental diagnostic value of 18 F-FDG PET and radiolabeled leukocyte scintigraphy in IE patients has already been reported. The aim of this study was to compare the respective performance of 18 F-FDG PET and leukocyte scintigraphy for the diagnosis of PVE in 39 patients. Methods: 18 F-FDG PET and leukocyte scintigraphy were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
120
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(163 citation statements)
references
References 15 publications
3
120
0
16
Order By: Relevance
“…10 In general, 18 F-FDG PET/CT affords a high sensitivity in the identification of PVE when echocardiographic results are inconclusive. 6,11 Yet, given the pitfalls leading to false-positive findings as described before, 9 the specificity of 18 F-FDG PET/CT in PVE detection may be limited, in particular within the first 2 months after surgical implantation. Albeit early identification of PVE is of utmost importance as these patients have a high mortality when not treated with geared antibiotics in a timely fashion, 12 the low specificity of 18 F-FDG PET/CT in PVE detection may lead to unnecessary surgical re-interventions not without risk.…”
Section: See Related Article Pp 1960-1967mentioning
confidence: 99%
“…10 In general, 18 F-FDG PET/CT affords a high sensitivity in the identification of PVE when echocardiographic results are inconclusive. 6,11 Yet, given the pitfalls leading to false-positive findings as described before, 9 the specificity of 18 F-FDG PET/CT in PVE detection may be limited, in particular within the first 2 months after surgical implantation. Albeit early identification of PVE is of utmost importance as these patients have a high mortality when not treated with geared antibiotics in a timely fashion, 12 the low specificity of 18 F-FDG PET/CT in PVE detection may lead to unnecessary surgical re-interventions not without risk.…”
Section: See Related Article Pp 1960-1967mentioning
confidence: 99%
“…7 Since then, multiple publications have included patients scanned less than three months (some less than two weeks) after implantation. [8][9][10][11][12][13][14][15] Some explicitly describe true negative findings in scans within this time frame, including our own study in the current issue. 10,12,15 In contrast, a recent study by Mathieu et al which included 51 patients without PVE showed that elevated uptake of FDG in the absence of infection can occur as late as 8 years after implantation, 13 and our own study showed false-positive late images in a patient 13 years after implantation.…”
mentioning
confidence: 99%
“…18,19 In cases where FDG PET/CT is difficult to interpret, additional radiolabeled leukocyte scintigraphy may help to further differentiate inflammation from infection: although at the cost of a lower sensitivity, its specificity is higher than that of FDG PET/CT. 8 Finally, it is essential to incorporate all available information in a multidisciplinary approach to establish a final diagnosis. 20 Rather than waiting 3 months to perform FDG PET/ CT in patients with a suspicion of PVE, we should be aware of the variable nature of FDG PET/CT findings in this setting.…”
mentioning
confidence: 99%
“…In a study of Rouzet F. et al a comparison of PET-CT with 18FDG and SPECT-CT with 99 mTc-HMPAOlabeled autoleukocytes for diagnoses of endocarditis was performed, and it was shown that the scintigraphy study had a significantly higher diagnostic efficiency compared to PET [82 ].…”
mentioning
confidence: 99%
“…This technique is successfully used to visualize the inflammation of various localizations and has high specificity -from 85% to 96% according to different authors [82,83,84]. At the same time, labeling of leukocytes in vitro, as was mentioned above, involves certain difficulties [50,51].…”
mentioning
confidence: 99%